INTERPRETASI GLOBAL HADIS RUKYAT HILAL - Rusmin, Pranoto Hidaya; Rohman, Arief Syaichu; Herdiwijaya, Dhani; Khaerani, Izzah Faizah Siti Rusydati; Pahlevi, Reza; Darmawan, Dadang (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2017)
Before Islamic Calendar begins, Muslims were used to wait for the earliest visible crescent (hilâl), which marks the beginning of Ramadan. The determination of the beginning of Ramadan is based on the rukyat al-hilâl hadith. Because the hilâl visibility on the earth surface is not the same, it results the differences on the beginning of Ramadan fasting. In addition, the sighting hilâl method can only determine the next 29 days, it cannot reach for the next month and even for the next year. These are the main reasons for re-interpretation of the rukyat al-hilâl hadith from global perspective. From this study, it is found that the context in the Qur?an, related to the Ramadan fasting, is fasting in one full month, 29 or 30 days, according to the duration of the lunar synodic cycle. However, the condition of the people and the science at that time has not developed yet, which is the cause of calculation (h}isâb) verses in the Qur?an cannot be used. When they have developed, the calculation verses in the Qur?an can be used to determine the number of days in a calendar month. This will produce a global calendar for mankind.